RELATIONSHIP BETWEEN KNOWLEDGE AND ATTITUDE OF DIABETES MELLITUS PATIENTS WITH DIABETIC FOOT ULCER TREATMENT IN SURGERY POLYCLINIC OF PARIAMAN REGIONAL HOSPITAL REGIONAL HOSPITAL - RAHMIWATI; ALPICES; DORA, MECHI SILVIA (Sekolah Tinggi Ilmu Kesehatan (STIKes) Piala Sakti Pariaman, 2025)
Diabetes mellitus is a serious health problem that can cause death and side effects on body parts. Common complications in people with diabetes are diabetic ulcers with a risk of death of around 25%. Good knowledge and attitude of ulcer care can improve care behavior and prevent early occurrence of diabetic ulcers. The purpose of this study was to determine the relationship between knowledge and attitude with diabetic foot ulcer care in people with diabetes mellitus at the Surgical Polyclinic of Pariaman Hospital. This type of research is quantitative research using a cross-sectional approach. This research was conducted at the Surgical Polyclinic of Pariaman Hospital on July 8-19, 2024. The sample in this study was 41 respondents. Sampling by accidental sampling. Statistical tests using the Chi Square test at the α level = 5%. The results of the study showed that the average respondent had sufficient knowledge, namely 19 people (46.3%), around 35 people (85.4%) respondents had a high attitude, and 33 people (80.5%) respondents carried out diabetic foot ulcer care well. The results of the Chi Square test on the aspects of knowledge and care of foot ulcers are p-value = 0.001 <α = 0.05, on the aspects of attitude and care of foot ulcers are p-value = 0.000 <α = 0.05. The conclusion of the study is that there is a relationship between knowledge and attitudes of diabetes mellitus sufferers with diabetic foot ulcer care at the Surgical Polyclinic of Pariaman Hospital. Suggestions, it is hoped that diabetes mellitus sufferers will always pay attention to the condition of their feet and take care of their feet to minimize the occurrence of wounds on the feet or can worsen diabetic ulcers.